Efficacy of a Decision Support Intervention on Decisional Conflict Related to Hepatocellular Cancer Treatment: A Randomized Controlled Trial. (January 2023) - Liao, Yueh-Ling; Wang, Tsae-Jyy; Su, Chien-Wei; Liang, Shu-Yuan; Liu, Chieh-Yu; Fan, Jun-Yu
The purpose of this study was to investigate the efficacy of decision support intervention on treatment knowledge, decision self-efficacy, decisional conflict, and decision satisfaction in patients with hepatocellular cancer. The study was a randomized controlled trial. In all, 69 patients with hepatocellular carcinoma (HCC) were recruited and randomly assigned to a decision support group or a control group. Data were collected at baseline, post-test, and follow-up using self-report questionnaires. After controlling for baseline scores, the between-group difference (95% confidence interval [CI]) for treatment-related knowledge in post-test scores was 11.9 (6.1, 17.8). After controlling for baseline scores, the between-group difference (95% CI) for decisional conflict was −7.0 (−12.0, −2.0). There was no statistically significant between-group difference in decision self-efficacy and decision satisfaction. Findings supported the efficacy of decision support intervention to improve treatment knowledge and reduce decisional conflict but had no significant effect on decision self-efficacy and decision satisfaction in patients with HCC.